Proteins that bind methylated DNA - Defossez, Pierre-Antoine (Henry Stewart Talks, 2011)
Introductory notions: distribution, abundance, and consequences of DNA methylation, The methyl-binding proteins: who they are, how they were found, What do the methyl-binding proteins do? Four examples, Unresolved questions and future perspectives, References